Analisis Profil Pelajar Pancasila Dalam Membentuk Sikap Toleransi Siswa Kelas IV Di SDN Bintara IV - Tazkiyah, Najwa; Awiria, Awiria (Department of Primary School Teacher Education, Faculty of Teacher Training and Education, Jambi University, 2025)
Research on the analysis of Pancasila student profiles in developing tolerance attitudes of fourth grade students at SDN Bintara IV shows that the role of educators is very important in planning intracurricular activities that contain Pancasila values. Through activities such as prayer, diversity discussions, and reflection, students are taught to recognize differences and develop tolerance attitudes. Although there are some negative actions, such as teasing and aggressive behavior, students show varying perceptions of tolerance, and teachers try to create a positive learning environment. With the right approach, students are expected to apply values ​​not only at school, but also in their daily lives. Analysis of Pancasila Student Profile in Developing Tolerance Attitudes among Fourth-Grade Students at SDN Bintara IV. This study uses qualitative research. Qualitative research is called a narutalistic research method, because it is carried out in natural conditions, without intervention from researchers. This study uses a descriptive approach, where the data collected is in the form of words or images so that it does not emphasize numbers. Data collection techniques include observation, interviews and documentation.